Anxiety and depression in patients with head and neck cancer: 6-month follow-up study - Wu Y; Lin P; Chien C; Fang F; Chiu N; Hung C; Lee Y; Chong M (Neuropsychiatric Disease and Treatment)
Yi-Shan Wu,1 Pao-Yen Lin,1,2 Chih-Yen Chien,3 Fu-Min Fang,4 Nien-Mu Chiu,1 Chi-Fa Hung,1 Yu Lee,1 Mian-Yoon Chong11Department of Psychiatry, 2Institute for Translational Research in Biomedical Sciences, 3Department of Otolaryngology, 4Department of Radiation Oncology, Kaohsiung Chang Gung Memorial Hospital, Chang Gung University College of Medicine, Kaohsiung, TaiwanObjective: We aimed to assess psychiatric morbidities of patients with head and neck cancer (HNC) in a prospective study at pretreatment, and 3 and 6 months after treatment, and to compare their health-related quality of life (HRQL) between those with and without depressive disorders (depression).Materials and methods: Patients with newly diagnosed HNC from a tertiary hospital were recruited into the study. They were assessed for psychiatric morbidities using the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, fourth edition. Their HRQL was simultaneously evaluated using the quality of life questionnaire of the European Organisation for Research and Treatment of Cancer with a specific module for head and neck cancer; and depressed and nondepressed HNC patients were compared by using the generalized mixed-effect model for repeated measurements.Results: A total of 106 patients were recruited into this study. High rates of anxiety were found at pretreatment, but steadily declined over time (from 27.3% to 6.4%, and later 3.3%). A skew pattern of depression was observed, with prevalence rates from 8.5% at pretreatment to 24.5% and 14% at 3 and 6 months, respectively, after treatment. We found that loss of sense (P=0.001), loss of speech (P<0.001), low libido (P=0.001), dry mouth (P<0.001), and weight loss (P=0.001) were related to depression over time. The depressed patients had a higher consumption of painkillers (P=0.001) and nutrition supplements (P<0.001). The results showed that depression was predicted by sticky saliva (P<0.001) and trouble with social contact (P<0.001) at 3 months, and trouble with social eating (P<0.001) at 6 months.Conclusion: Patients with HNC experienced different changes in anxiety and depression in the first 6 months of treatment. Dysfunction in salivation, problems with eating, and problems with social contacts were major risk factors for depression.Keywords: depression, anxiety, quality of life